Is peritoneal dialysis feasible after laparotomy in children? A case-control series to compare outcomes. Issue 6 (December 2017) - Bouty, A.; Faure, A.; Shaw, L.; Ah Toy, J.; Dobremez, E.; O'Brien, M.; Heloury, Y.
Summary: Objectives: Peritoneal dialysis (PD) is the modality of choice for children with end-stage renal disease (ESRD) awaiting renal transplant; however, this option is sometimes avoided for those with previous laparotomy. The goal of this study was to compare the outcomes of PD in patients with and without previous laparotomy. Patients and methods: Twenty-four patients who had been started on peritoneal dialysis were retrospectively analysed. Group LAP consisted of six patients with previous laparotomy, and Group NO-LAP of 18 controls with either retroperitoneal or no abdominal surgery. The percentage of theoretical maximum volume of infusion, time to reach it, complications (infection and drainage difficulties), and number of catheters needed to finish therapy were analysed. Results: The characteristics of patients and technique of insertion are presented in Table. The percentage of maximum theoretical volume of infusion was similar in both groups. Median of catheter survival was similar in both groups. Complications were divided into malfunction (slow drainage, obstruction or leak) and infection. Incidence of complications per catheter and per month of dialysis was ten times lower in Group NO-LAP. Peritoneal dialysis failed in one patient with recurrent intraperitoneal adhesions after adhesiolysis in Group LAP. Conclusion: Despite a higher incidence of complications (malfunction and infections), PD remains an acceptable option after laparotomy. In this series, it was sufficient in achieving adequate filtration in five patients. Table Characteristics of patients, details of catheter use and complications, and overall efficacy of PD in both groups. Total 24 patients Median age (m) at insertion Median weight (kg) at insertion Technique of insertion: laparoscopic Median delay before 1st use (d) Median percentage of maximum theoretical volume Complications Median of catheter survival (m Efficacy 1400 ml/m 2 if >2 y 40 ml/kg Malfunction Infection 800 ml/m 2 if <2 y LAP ( n  = 6) 114 (5.5 m–15 y) 24.6 (3.8–37.5) 4 patients 1.5 (1–3) 86% 83% 1 per 23 months of dialysis 0.01 per catheter per month 1 per 17 months of dialysis 0.01 per catheter per month 12 m (1 w–2 y) 5 of 6 patients NO-LAP ( n  = 18) 133.5 (1 w–16.5 y) 33.1 (4–41.8) 14 patients 1 (1–45) 77% 86% 1 per 31 months of dialysis 0.001 per catheter per month 1 per 27 months of dialysis 0.001 per catheter per month 11.5 m (2 w–3 y) 18 of 18 patients